Association between FLT3-ITD and additional chromosomal abnormalities in the prognosis of acute promyelocytic leukemia. Issue 12 (December 2022) - Vu, Minh Phuong; Nguyen, Cuc Nhung; Vu, Hoang; Nguyen, Tuyet Mai; Nguyen, Tuan Tung; Pham, Phuong Thao
Objectives: Internal tandem duplications of the Fms-like tyrosine kinase 3 gene ( FLT3-ITD) and additional chromosomal abnormalities (ACA) are prognostic factors in patients with acute promyelocytic leukemia (APL). This study aimed to determine the effect of the association between FLT3-ITD and ACA in the prognosis of APL. Methods: This was a retrospective cohort study including 60 patients with APL treated with all-trans retinoic acid (ATRA) and chemotherapy. Five-year overall survival (OS) and progression-free survival (PFS) were analyzed in patient groups according to the presence of FLT3-ITD and ACA. Results: FLT3-ITD was an independent adverse factor for 5-year PFS, and ACA was an independent adverse factor for 5-year OS. There were significant differences in OS and PFS among the groups: FLT3-ITD -negative without ACA, FLT3-ITD -positive without ACA, FLT3-ITD -negative with ACA, and FLT3-ITD -positive with ACA. The OS times were 52.917, 45.813, 25.375, and 23.417 months, and the PFS times were 48.833, 38.563, 23.250, and 17.333 months, respectively. Conclusion: FLT3-ITD and ACA are associated with the poorest OS and PFS outcomes in patients with APL treated with chemotherapy plus ATRA.